METAKELAS AND STUDENT TECHNOLOGY ACCEPTANCE: TRANSFORMING ONLINE CLASS USING METAVERSE LEARNING ADOPTION BASED ON PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND BEHAVIORAL INTENTION - Abd Razak, Abd Hadi; Ismail, Syamsyul Anuar; Mohamed, Nur Fadziana Faisal; Ibrahim, Marzura; Mohmad Yazam, Siti Syamsul Nurin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The COVID-19 pandemic accelerated the adoption of online learning platforms, yet traditional video conferencing tools have proven inadequate in sustaining student engagement, presence, and cognitive focus. This study examines student acceptance of MetaKelas, a browser-based metaverse learning platform, through the lens of the Technology Acceptance Model (TAM). The primary objective was to investigate how perceived usefulness, perceived ease of use, and attitude toward use influence behavioural intention to adopt metaverse platforms in higher education. A quantitative quasi-experimental post-test only design was employed, involving foundation and undergraduate students at Universiti Utara Malaysia who used MetaKelas across two consecutive academic semesters (A241 and A242). Data were collected through structured online questionnaires measuring TAM constructs using seven-point Likert scales and analysed using partial least squares structural equation modelling (PLS-SEM). The measurement model demonstrated excellent reliability and validity, with all constructs exceeding recommended thresholds for internal consistency (CR > 0.95) and convergent validity (AVE > 0.81). The structural model exhibited substantial explanatory power, with R² values of 0.733 for attitude and 0.769 for behavioural intention. Results revealed that perceived usefulness significantly predicted attitude toward use (β = 0.650, p = .005), while perceived ease of use showed no significant effect (β = 0.230, p = .298). Attitude strongly predicted behavioural intention (β = 0.877, p < .001) and significantly mediated the relationship between perceived usefulness and behavioural intention (β = 0.570, p = .005), but not between perceived ease of use and behavioural intention (β = 0.202, p = .303). These findings suggest that among digitally fluent students, demonstrating educational value matters more than interface simplicity in driving metaverse adoption. The study contributes empirical evidence supporting TAM’s applicability to immersive learning environments and offers practical implications for educators and instructional designers seeking to implement accessible, avatar-based platforms as scalable alternatives to traditional video conferencing in online education.